Best practice recommendations for healthy work environments for nurses: An integrative literature review - Mabona, Jean F.; van Rooyen, Dalena; ten Ham-Baloyi, Wilma (Health SA = SA Gesondheid, 2022)
Healthy work environments that maximise the health and well-being of nurses are essential in achieving good patient and societal outcomes, as well as optimal organisational performance. While studies have been conducted on healthy work environments, there is no available evidence that an integrative literature review summarising best-practice recommendations related to healthy work environments has been conducted before. This review aimed to summarise existing best-practice recommendations related to a healthy work environment for nurses. An integrative literature review following the approach adapted from Whittemore and Knafl was used. Existing guidelines related to healthy work environments for nurses were searched. EBSCOhost (CINAHL, Medline), Biomed Central, Science Direct, PubMed and Google Scholar and organisational websites via Google were searched, followed by a citation search. Twelve guidelines were identified for data extraction and synthesis, and themes were subsequently formulated. Four themes emerged from the integrative literature review regarding a healthy work environment for nurses: (1) the need for effective nursing leadership, (2) effective communication as central to enhancement of a healthy environment, (3) effective teamwork as an integral part of a healthy work environment and (4) the need for professional autonomy. In summary, a healthy work environment for nurses requires leadership, effective communication, teamwork and professional autonomy.ContributionThe findings can be used to conduct quality studies related to healthy work environments for nurses in comprehensive health care settings, particularly those dealing with resource constraints. This can inform evidence-based recommendations and guidelines in these settings, as such guidelines are currently lacking.